Faktor-Faktor yang Memengaruhi Sikap dan Niat Perilaku Mahasiswa pada Pembelajaran Daring di Perguruan Tinggi - Wijaya, Geraldi; Taslim, Michelle Chrisca; Yosevina, Christiana Tercia; Amelia, Novi (Universitas Prasetiya Mulya, 2025)
The study aims to identify and analyze the factors that are influencing students’ attitudes and behavioral intention toward online learning in higher education institutions. Focusing on variables that have been researched before toward attitude such as Perceived Usefulness, Perceived Ease of Use, Social Influence, Educational and Environmental Conditions, Self Efficacy, and Mindful Agency, this research aims to understand the relationship between these factors and students’ attitudes toward the use of online learning. Primary data was collected from a Google Form questionnaire shared to 200 Indonesian students who have experienced online learning during the pandemic or continue to do so until now. these findings provide deep insights into the factors influencing students’ attitudes and behavioral intentions towards online learning. They can help educational institutions design more effective strategies tailored to students’ needs in the implementation of online learning in the future.